2006
DOI: 10.4012/dmj.25.684
|View full text |Cite
|
Sign up to set email alerts
|

Plasma-based Fluorine Ion Implantation into Dental Materials for Inhibition of Bacterial Adhesion

Abstract: The aims of this study were to evaluate the fluorine depth profiles of pure titanium (Ti) , stainless steel (SUS) , and polymethyl methacrylate(PMMA)modified by plasma-based fluorine ion implantation and the effects of fluorine ion implantation on contact angle, fluoride ion release, and S. mutans adhesion. Fluorine-based gases used were Ar+F 2 and CF 4 . By means of SIMS, it was found that the peak count of PMMA was the lowest while that of Ti was the highest. Then, up to one minute after Ar sputtering, the p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
14
0

Year Published

2008
2008
2020
2020

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 36 publications
(15 citation statements)
references
References 46 publications
0
14
0
Order By: Relevance
“…However, corrosion of titanium by anti-carious agents containing fluoride has been reported [ 25 ]. Additionally, it was observed that the surface of titanium plate became discolored and corroded after plasma-based fluorine ion implantation in our previous study [ 14 ]. Therefore, titanium can only be implanted with Ag; thus, in the present study, the effectiveness of only Ag ion implantation is additionally examined to determine the applicability of this method to various materials in the future.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, corrosion of titanium by anti-carious agents containing fluoride has been reported [ 25 ]. Additionally, it was observed that the surface of titanium plate became discolored and corroded after plasma-based fluorine ion implantation in our previous study [ 14 ]. Therefore, titanium can only be implanted with Ag; thus, in the present study, the effectiveness of only Ag ion implantation is additionally examined to determine the applicability of this method to various materials in the future.…”
Section: Discussionmentioning
confidence: 99%
“…In PBII, even a three-dimensional sample having a complex shape can be implanted ions into the surface with good compatibility and uniformity without beam scanning or special target manipulation. In our previous work, an approach to induce antimicrobial properties on a PMMA surface by modifying the material surface using the PBII method was proposed [ 14 , 15 , 16 ], and it was demonstrated that fluorine (F) and silver (Ag) ion implantation inhibited the growth of general bacteria, Staphylococcus aureus ( S. aureus ), on the PMMA surface [ 16 ]. However, how this method affects oral microorganisms was not verified.…”
Section: Introductionmentioning
confidence: 99%
“…As stated previously, zirconium, silicon and fluorine enriched layer formed during the sandblasting and the reaction with HNO 3 /HF solution. It has been clearly demonstrated in recent years that zirconium [53], silicon [54] and fluorine [55] incorporated surfaces that can have strong anti-bacterial and anti-infection effects on biofilm development on implant surfaces and improve the biological capability. Fluoride has been known for its bactericidal effect by the disruption in metabolism because of the inhibition of bacterial enzymes and membrane function [55,56].…”
Section: Microbiological Studiesmentioning
confidence: 99%
“…It has been clearly demonstrated in recent years that zirconium [53], silicon [54] and fluorine [55] incorporated surfaces that can have strong anti-bacterial and anti-infection effects on biofilm development on implant surfaces and improve the biological capability. Fluoride has been known for its bactericidal effect by the disruption in metabolism because of the inhibition of bacterial enzymes and membrane function [55,56]. Recently, silicon and fluoride ions have been reported to enhance the incorporation of newly formed collagen into the bone matrix and increase the rate of seeding of apatite crystals [57,58].…”
Section: Microbiological Studiesmentioning
confidence: 99%
See 1 more Smart Citation